Implementasi Infografis Sebagai Upaya Peningkatan Penjualan Masa Pandemi Covid-19 (Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
The current condition of the Covid-19 pandemic, some of the MSME sectors in the food industry, especially tofu, have decreased in income levels, MSMEs in the tofu industry are Berkah Sejahtera in West Sulawesi Province which are experiencing an income crisis. So to help generate these businesses, the purpose of the service is the implementation of infographics as an effort to increase sales during the COVID-19 pandemic, the tofu industry is blessed with prosperity in the West Sulawesi region. Through mentoring and training methods for making infographics with stages and uses that are easy to implement. Based on the graph of the growth of the Berkah Sejahtera tofu industry in 2016 to 2018 there was an increase in production that was perfectly elastic as well as in 2019 to 2021 the production volume had increased, with the application of an infographic system helping this industry in the sales system and product introduction. Revenue gains in the Berkah Sejahtera tofu industry in 2016-2018 amounted to Rp. 2,439,540,000 and in 2019-2021 it was Rp. 2,153,940,000. Changes in raw material prices are the main focus for the Berkah Sejahtera tofu industry, especially soybeans